'Crop Raiding': Farmers' Perspectives in Shiwalik Hills of North-Western Himalayas, India. Issue 4 (2nd October 2022) - Kumar, Vijay; Attri, Varun; Rana, D. S.; Chauhan, S. K.
Abstract: A study was conducted to ascertain the causes and possible strategies to mitigate the problems of human–animal conflicts in the foothills of the Shiwaliks of the North-Western Himalayas, known as the Kandi region in the Punjab state of India. The main causes of 'crop raiding' were a reduction in grazing areas due to the impacts of deforestation, and reduced numbers of predatory carnivores, lantana infestation in the forests and the overexploitation of the forests for wild fruits. It was observed that neelgai and wild boars are the dominant species in the areas adjoining forests, while and stray cattle are dominant in areas outside forests. Traditional methods being adopted by the farmers for curbing these problems were not effective against most of these species. Classifying some animals as vermin, sterilizing monkeys, payment of compensation to affected farmers, strict implementation of wildlife laws and lantana eradication were suggested as the possible strategies for minimizing losses due to crop raiding.